The Effectiveness and Practicality of Web-based Learning Media with Wix Platform in Vocational High Schools - Umamah, Chairatul; Diraya, Inayatun; Andi, Herman Jufri (Universitas Muhammadiyah Makassar, 2023)
Learning media is one of the instruments which is used to support the achievement of learning process. Now, the use of learning media based on technology is widely used at various levels of education based on school needs. One of the learning media used in this study is Wix platform. The purpose of this study was to describe and measure the effectiveness and practicality of using the web-based learning media with Wix platform in vocational high schools. This type of research is research and development employing Borg and Gall development model. The research subjects consisted of media experts, material experts, and sample class consist of 19 students of X class at SMKN 1 Pakong. In this study, the effectiveness of learning media is measured by students’ learning outcomes before and after using learning media. The media practicality questionnaire for teachers was used to collect data as teacher responses after testing the media product developed in the form of web with Wix platform. The results of the research show that the practicality percentage of Wix platform as physics learning media was 95.7% which is categorized as